Tensions in Stakeholder Theory. Issue 2 (February 2020) - Freeman, R. Edward; Phillips, Robert; Sisodia, Rajendra
A number of tensions have been suggested between stakeholder theory and strategic management (SM). Following a brief review of the histories of stakeholder theory and mainstream SM, we argue that many of the tensions are more apparent than real, representing different narratives about stakeholder theory, SM, business, and ethics. Part of the difference in these two theoretical positions is due to the fact that they seek to solve different problems. However, we suggest how there are areas of overlap, and we argue that some of the tensions may, instead, provide interesting ways to put the two areas of scholarship and practice together. We maintain that SM and stakeholder theory could mutually benefit from a more pragmatist philosophy.